2020
DOI: 10.1080/13467581.2020.1799798
|View full text |Cite
|
Sign up to set email alerts
|

Gazing behavior exhibited by people with low vision while navigating streets

Abstract: "Low vision" is defined as uncorrectable vision loss that interferes with daily activities. The gazing behavior exhibited by people with low vision as they walk is particularly important because it illustrates how they utilize information in various environments. In this study, eight participants with low vision and eight fully sighted participants were asked to navigate a roadway and a sidewalk wearing a mobile eye-tracking device. Their gazing behavior and walking behavior were recorded and analyzed. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…43 Although this was shown in only one study, and this study only measured performance in individuals with central vision loss, other studies reported similar results with low-vision individuals (both peripheral and central vision loss). Matsuda and colleagues 62 reported that individuals with low vision tend to keep their gaze lower than individuals with normal vision when walking along a roadway and a sidewalk and were more likely to gaze on environmental objects on the road, such as the lane markings while navigating. Freedman and colleagues 63 reported that, while walking along an indoor obstacle course, individuals with low vision spent more time focusing their gaze on the intersections of an environment, such as where the floor and wall meet, compared with individuals with normal vision wearing glasses that blurred vision.…”
Section: Discussionmentioning
confidence: 99%
“…43 Although this was shown in only one study, and this study only measured performance in individuals with central vision loss, other studies reported similar results with low-vision individuals (both peripheral and central vision loss). Matsuda and colleagues 62 reported that individuals with low vision tend to keep their gaze lower than individuals with normal vision when walking along a roadway and a sidewalk and were more likely to gaze on environmental objects on the road, such as the lane markings while navigating. Freedman and colleagues 63 reported that, while walking along an indoor obstacle course, individuals with low vision spent more time focusing their gaze on the intersections of an environment, such as where the floor and wall meet, compared with individuals with normal vision wearing glasses that blurred vision.…”
Section: Discussionmentioning
confidence: 99%
“… 21 23 Studies that involved pedestrians with vision impairment focused on specific scenarios like street crossing 24 26 or on environmental aspects, such as urban design. 27 What little data exist regarding naturalistic gaze scanning in pedestrians with HH, comes from our preliminary analysis of the pilot data 28 from a study of eye-in-head movement of 3 patients with HH, 29 and from our recent report of gaze scanning by the same pedestrians with HH at street crossings, where we found evidence of compensatory gaze scanning. 30 …”
mentioning
confidence: 94%